Axiology of Payables And Receivables In The Perspective of Sharia Finance Accounting - Luthfia, Nadira; Purbaningrum, Ivana Rosa; Nasim, Arim; Suryadi, Edi (Program Pascasarjana UIN Sumatera Utara, 2024)
Axiology in the context of financial accounting for debt and receivables transactions involves the application of ethical principles, moral values, and philosophical values in the management and reporting of debt and receivables. In the Islamic perspective, the axiology of financial accounting for debt and receivables becomes a profound study by applying Sharia principles as the main guidance. One of the fundamental principles that serves as a foundation is the prohibition of usury (riba). This research employs a qualitative research method in the form of a literature review with a systematic reviews approach. The data used in this research refer to books and research articles. Data search is conducted using keywords such as